Benefits and Problems of Using Learning Applications in Teaching English - Joko Prayudha.S (Datokarama English Education Journal, 2024)
This research describes the benefits and problems of teaching English using learning applications. This research is library research. The analysis shows that teaching English using learning technology has several benefits in the teaching and learning process, such as helping students understand the material more easily, increasing interest and motivation in learning, building self-confidence, training cooperation, increasing critical thinking, and creating an atmosphere where learning becomes more fun. For example, in learning speaking, teachers can use social media platforms to practice their English speaking skills, such as by recording videos on YouTube, voice recordings on WhatsApp Voice and so on. Besides that, several difficulties when teaching English using learning applications are time management, difficulty developing material, and students failure to focus on certain parts of learning. In this technology-based learning environment, it is necessary for the teacher to provide clear instructions to students regarding the use of learning applications so that the activity process can be carried out properly and appropriately. To be successful in teaching English by using learning applications, several aspects must be considered that involve all parties, including the availability of infrastructure and devices, the readiness of learning materials, learning activities that support students' cognitive development, and the readiness of teachers and students to carry out various learning applications.